The 'Myth' of the Clash of Civilisations: Intercultural Communication and Reconciliation - Tan, Yiqiao (Journal of Humanities and Social Sciences Studies, 2024)
The theory of the Clash of Civilisations, which posits the existence of irreconcilable contradictions and conflicts among civilizations, has a positive significance; however, this viewpoint fails to acknowledge the commonalities and interdependence among civilizations. This paper begins by examining the genesis and evolution of the Clash of Civilizations Theory, encompassing a review of its theoretical underpinnings and practical ramifications. It then delves into the ongoing debate surrounding the Clash of Civilizations Theory and the perspectives of prominent scholars. Subsequently, the paper introduces the distinction between cultural differences and the clash of civilizations and analyses the relationship between the two. Subsequently, the concept of cross-cultural communication and reconciliation is introduced, and the ways in which the clash of civilizations may be mitigated by promoting dialogue, understanding, and cooperation among civilizations are discussed. In conclusion, the paper puts forward solutions that are currently being implemented, such as the concept of building a community of human destiny, with the aim of promoting cross-cultural communication and reconciliation. This will provide inspiration and guidance for the creation of a harmonious global society. Furthermore, the paper anticipates the future development of civilizational symbiosis and emphasizes the necessity and possibility of establishing harmonious international relations.